Exploring diversity in expert knowledge: variation in local ecological knowledge of Alaskan recreational and subsistence fishers. (24th December 2018) - Chan, Maggie N; Beaudreau, Anne H; Loring, Philip A
Abstract: Local ecological knowledge (LEK) of resource users is a valuable source of information about environmental trends and conditions. However, many factors influence how people perceive their environment and it may be important to identify sources of variation in LEK when using it to understand ecological change. This study examined variation in LEK arising from differences in people's experience in the environment. From 2014 to 2016, we conducted 98 semi-structured interviews with subsistence fishers and recreational charter captains in four Alaskan coastal communities to document LEK of seven fish species. Fishers observed declines in fish abundance and body size, though the patterns varied among species, regions, and fishery sectors. Overall, subsistence harvesters provided a longer-term view of abundance changes compared with charter captains. Regression analyses indicated that the extent of people's fishing areas and their years of fishing experience were relatively important factors in explaining variation in fishers' perceptions of fish abundance. When taken together, perspectives from fishers in multiple regions and sectors can provide a more complete picture of changes in nearshore fish populations than any source alone. These findings underscore the importance of including people with different types of expertise in local knowledge studies designed to document environmental change.